Zones of contention : essays on art, institutions, gender, and anxiety - Becker, Carol (SUNY series, interruptions--border testimony(ies) and critical discourse/s., 1996)
This collection of essays by cultural critic Carol Becker plumbs particular areas of controversy to understand what information these "zones of contention" might yield about the multifarious culture wars taking place within American society today. In the process she addresses the place of art and artists in society, the difficulties facing women in the workplace, why male bonding exists, why women experience anxiety in relationship to creative endeavors, and why artists are misunderstood within American society. She positions art and artists, as well as institutional dynamics within a philosophical framework.